Psychological Obstacles in Second Language Acquisition and How to Overcome Them - Imas Komala; Yusak Hudiyono (Green Publisher Indonesia, 2025)
Second language (L2) acquisition is often confronted with various psychological barriers that can hinder the learning process. These barriers include anxiety, embarrassment, fear of making mistakes, and lack of motivation. These psychological factors can affect learners' self-confidence and slow down their ability to master a second language. This study discusses the common psychological obstacles faced by L2 learners and how to overcome them. Proposed solutions include stress management techniques, enhancing intrinsic motivation, and creating a supportive learning environment. This research aims to provide insights for language teachers and learners in tackling these psychological challenges with more effective approaches.